The First Extremist Sect in the Muslim World: Al-azariqa - Shirinov, Agil (Scholarya Demo Journal of Ruby, 2020)
Al-Azraqiyya (Azariqa) is considered as one of the radical sects in Islamic History. This sect, which was one of the branches of Khavarij took an exclusivist stand against those who did not accept their views and even declared them as unbelievers. The Azariqa, which was formed on the bases of Nafi ibn al-Azraq’s views, tended to violent extremism as well as the representatives of the sect revolted in many cities and regions of the Islamic world such as Basra, Khuzistan, Ahwaz, Tabaristan, Fars, Isfahan, etc. The article discusses the activities of Nafi ibn al-Azraq as well as the major beliefs of al-Azariqa. It is pointed in the article that the beliefs such as the children and wives of those who disagree with Azariqa could be killed as well as the children of their opponents would go to the everlasting hell together with their parents, he impermissibility of taqiyya in word or deed, etc., were among the major beliefs of al-Azariqa. It is also investigated the major factors responsible for the formation al-Azariqa and its adoption of the views based on violence. In the article, along with the sources of the History of Islamic Denominations such as Abul-Hasan al-Ash’ari’s Maqalat al-Islamiyyin, Malati’s at-Tanbih wa ar-Radd 'ala Ahl al-Ahwae wal-Bida' , Abd al-Qahir al-Baghdadi’s al-Farq bain al-Firaq, Abu al-Fath al-Shahristani’s al-Milal wa an-nihal, Ibn Hazm al-Andalusi’s al-Fasl fi ' l Milal wa ' l Ahwa ' wa ' l Nihal the sources of the History of Islam such as Ibn Jarir al-Tabari’s Tarikh al-Rusul wa al-muluk, Ibn Athir’s al-Kamil fi at-Tarikh and Ibn al-Kathir’s alBidaya wa an-Nihaya, which is related to the subject, have been also used.